Kemampuan ICT Guru pada Pembelajaran Daring di Pondok Pesantren Al-Ihsan Boarding School (IBS) Kabupaten Kampar Provinsi Riau - Rifaldi (Milenial: Journal for Teachers and Learning, 2024)
This study aims to determine the ICT ability of teachers in online learning at Pondok Pesantren Al-Ihsan Boarding School (IBS) Kampar Regency. This research method is qualitative method. The subject of this research is the master at the Al-Ihsan Boarding School (IBS) boarding school in Kampar Regency, Riau Province totaling 47 people. These data were collected from interviews, questionnaires and observations with data processing techniques using descriptive methods. The results of the research found that there were ICT skills of teachers at Pondok Pesantren Al-Ihsan Boarding School (IBS) Kampar Regency were in the medium category as much as 38.3%. The need to improve the quality of the teacher's ICT ability so that it can be useful to be applied in all fields of study within the scope of the school.